Analysis of the Judge’s Decision Regarding the Blasphemy Case (Case of Decision 726/Pid.Sus/2023/PN Plg) - Zulaikha, Almira Novia; Maftuhah, Zahra (Universitas Negeri Semarang, 2023)
This research delves into the intricate and significant landscape of religious blasphemy cases, a phenomenon on the rise in Indonesia. Beyond causing societal disturbances, these cases pose substantial challenges within the legal and judicial framework. The escalating number of such cases reflects a noteworthy expansion in the diversity of opinions and expressions within society. However, the lack of clarity in the legal boundaries surrounding religious blasphemy often leads to uncertainty in establishing guilt and determining appropriate punishment, despite existing regulation in the Information and Electronic Transactions Law. The influence of media and social media exacerbates the complexity of religious blasphemy cases. Coverage and discussions on online platforms play a pivotal role in shaping public opinion and influencing the trajectory of the judicial process. This impact extends beyond the national level, potentially sparking global ramifications. Concurrently, judicial independence faces scrutiny, as external pressures from various entities can sway judges' decisions. Consequently, this research seeks to provide a thorough understanding of these multifaceted aspects. An analysis of the judge's decision in the religious blasphemy case, as exemplified by Lina Mukherjee on social media, becomes crucial for dissecting the legal and social dynamics at play. This examination not only aims to comprehend the intricacies involved but also serves as a foundation for proposing recommendations to enhance the justice system. The ultimate goal is to achieve a balance in justice and safeguard human rights in the face of evolving challenges posed by religious blasphemy cases.